Danielle K. answered • 05/02/13

Customized Lessons, Patient, Effective, Experienced Math Tutor

Absolutely!

The simplest method is using the Quadratic Formula! Or at least that is my favorite!

x = [-b ± √(b^{2} - 4ac)]÷[2a]

**Example 1:** Let the equation be 3x^{2} + 11x - 4

Then ... a = 3, b = 11, c = -4

x = [-11 ± √(11^{2} - (4)(3)(-4))]÷[(2)(3)]

x = [-11 ± √(121 + 48)]÷[6]

x = [-11 ± √(169)]÷[6]

x = [-11 ± 13]÷[6]

x = [-11 + 13]÷[6] or x = [-11 - 13]÷[6]

x = 1/3 or x = 4

Now the factors will be ...

= (x - 1/3)(x - 4)

or

= (3x - 1)(x - 4)